... (2x-y)^3+3(2x+y)(4x^2-2xy+y^2)-6xy(3y-6x) Annchen хорошист ... - Read more

... (4x^2-y^2)/(8x^2+10xy+3y^2)*(4x^2-9xy-9y^2)/(2x^2-5xy-3y^2)} ... (y 2))) 2x+y Step 2 : 4x 2 - y 2 Simplify ... 2x-y 4x+3y Multiply ...

2. 2x-y=6-x+y=-1 Substitution method: ... 2x - y = 6 2x - (-1 + x) = 6 2x + 1 - x = 6 x + 1 = 6 x = 6 - 1 x = 5 3. ... Multiply each equation by whatever number is ...

Simple and best practice solution for y=-3/4x-3;y=1/2x+2. ... Remember to put linear equations with variables x and y. for example: 2x+y=8 x+3y=14

Multiply: 5xy(2x - y) Log In Sign Up MyFeed Find People Account Archive Help Blog About. Log In Sign Up MyFeed Find People More > < Back Account Archive Help Blog ...

multiply 2x/4x+2 by 14x+7/4. asked Apr 26, 2012 in Algebra 2 Answers by anonymous. ... what is 2x+y=3 -2x+5y=-9. asked Nov 5, 2013 in Algebra 2 Answers by anonymous.

2x-y = 5. 2x + x - 3 = 5. We'll combine like terms: 3x - 3 = 5. We'll add 3 both sides: ... We'll multiply -3 by 3: (8-9)/3 = -y-1/3 = -y. We'll multiply by -1 both ...

1.（2x-y)(4x^2-y^2)(2x+y) 2.(1+x)(1-x)(1+x^2)(a+x^4) 3.方程（x+3）（2x-5）-（2x+1）（x-8）=41的解 你尝试着化简 1.(2x-y)(2x+y)=4x^2-y^2 原式 ...

(-1/2x+y)( )=1/4x^2-y^2. ... [（2x-y）（2x+y)] }×[-( 2x+y)]= -1/（2x-y）=1/（y-2x) qzgqq ...

2x + y = 1 x^2 + y^2 = 1 (This is the Unit Circle for Trig.) x^2 + (1 - 2x) ... Let's take the second equation and replace y with (1-2x)... x^2 + y^ 2 = 1. x 2 +(1-2x ...

... (x * x 2 + x * y + 5x) + 3x 2 + 3y + 3 * 5 = x 3 + xy + 5x + 3x 2 + 3y + 15 ... Question 2: Multiply (x 2 + 2x + 4) and (x 2 + 6x + 5) Solution: (x 2 + 2x + 4 ...

[(4y 2 +x 2 +4xy)(2y-x)] + [(4x 2 +y 2 +4xy)(2x-y)] [8y 3 +2x 2 y+8xy 2-4xy 2-x 3-4x 2 y] + [8x 3 +2xy 2 +8x 2 y-4x 2 y-y 3-4xy 2] [8y 3-x 3-2x 2 y+4xy 2] + [8x 3-y 3 ...

∵1/4x^2-y^2=(-1/2x+y) ... [（2x-y）（2x+y)] }×[-( 2x+y)]= -1/（2x-y）=1/（y-2x) ... 1回答 1.multiply the mononomial and the polynomial.Assu;

4x^2-y^2=(2x-y)()4x^2-y^2=(2x-y)(2x+y) ... 2014-05-25 计算：(4x^2-y^2)÷4x^2-4xy y^2/2x-... 2014-05-20 [(2x+y)的2次方-y(y+4x)-2x]÷2x= 要过...

已知：（2x-y-1）2+sqrt{xy-2}=0，（1）求frac{y-2x} ... （2）求4x 3 y-4x 2 y 2 +xy 3 ... 分析：先根据平方与二次根式的非负性得出2x-y=1 ...

2x 2x y=2x-5 Like; Report. 1 comment | Post one | Permalink. by bee bee on November 8th, 2009 2x+y=5. Like; Report. No comments ...

4x^2-y^2+2x+y 因式分解，要过程。 =(2x+y)*(2x-y)+(2x+y) =(2x+y)*(2x-y+1)

y = 4x 2, 2x + y = 6. Calculus. Answers (2) answered 3 years ago View this solution... try Chegg Study. Access this solution and millions more, plus ask our experts ...

（1/2x+y）（1/2x一y）（1/4x^2一y^2 ... （1/2x+y）（1/2x一y）（1/4x^2一y^2）=（1/4x 2_y 2 ...

... -y=-2x+4then multiply by -1 to make the y positive ... 1.2x-y=4 2.2x-3y=4 Thank Writer; Comment; Blurt; thanked the writer. blurted this. Anonymous answered . 3y ...

2x + y = 3 --- (1) 4x + 4y = 8 --- (2) From (2), we have: ... Substituting (3) into (1), we will get: 2x + 2 - x = 3 x = 3 - 2 x = 1 Substituting x = 1 into (3), we ...

... If 2x-y=4 then 6x-3y=? (a)15 (b)12 (c)18 (d)10 . ... 2x-y = 4 multiply with 3 on both sides 3(2x-y) = 3*4 ... given 2x-y=4 => y=2x-4 put this in second eq then 6x

2x-y＝2，y=2x-2，带入4x^2＝y^2-12得可一算得x=-1,进而y=-4故，x+y=-5 ...

（2）（2x+y）（2x-y）+（-x）（4x-y） =4x 2-y 2-4x 2 +xy =-y 2 +xy ... （4）（-3x 2 y 3 ） 2 •（-2x 3 y 2 ...

... -2x + y + z = -2 5x + 3y + 3z = 71 4x -2y -3z = 1, Topics: Math, Tags: algebra 2, Math. ... y + z = -2 + 2x. and (2) gives y ... multiply (i)by 3 and add to (iii ...

... (4x 2-y 2)/(x 2 y-xy 2)* ... (2x-y) Step 4 : 4x 2 - y 2 Simplify ————————— x 2 y ... (2x-y) x+y Multiply ...

Related Questions

Recent Questions

... 2x + y = 4 ab) h: 2x + y = 10 ac) l: 2x + y = 14 ... ² + ( y +2)= 20 Ich setze 4-2x für y ein: x= (x +1)² + ( y +2)= 20 x= (x +1)² + ( 4-2x +2)= 20 - Read more